Microbial Biomass and Soil C, N and P in Acacia nilotica sub. Cupressiformis Based Traditional Agroforestry Systems in Rajasthan - Mehar, Santosh K.; Purohit, Usha; Sundaramoorthy, S. (Indian Journal of Agroforestry, 2020)
Study of temporal patterns of microbial biomass can help in understanding the functioning of various ecosystems. In the present study an attempt has been made to study the influence of trees on the microbial biomass and soil C, N and P levels with an accompanied attempt to find the temporal variables influencing it. Three sites with Acacia nilotica sub. cupressiformis as the woody component in the traditional agroforestry systems of Indian arid zone were selected and studied for the spatial and temporal variation in microbial biomass and soil nutrients over a period of two years. Soil samples were collected from both the undercanopy and the open area. Higher values of microbial and soil nutrients were recorded during monsoon, post monsoon and winter seasons, reflecting the role of moisture availability on the functioning of dryland agroecosystems. Soil nutrients serving as resource for the microbial biomass revealed strong relationship; organic C with biomass C (r = 0.44; P